A graduação em Medicina: um relato de experiência - Rossi, Giulia Zanata (Universidade Federal de São Carlos, 2021)
The graduation in medicine at the Federal University of São Carlos marked a period of great discoveries and personal and professional growth. Taking care of people is a privilege that involves a lot of seriousness, dedication to studies and skills to be achieved. This Course Conclusion Work is based on a reflective narrative referring to my trajectory in the medical course at the Federal University of São Carlos, which was divided into three cycles lasting two years each. During the last cycle of graduation, I experienced the beginning of the COVID-19 pandemic, which was a remarkable period of great uncertainty, many adaptations to the new reality and great growth in medicine. In addition to academic training, this narrative refers to experiences during further training, and at the end there is a memorial about all activities developed during graduation. I am very proud and feel secure in receiving a medical degree to be able to practice this profession, which for me is so wonderful and full of possibilities.
Graduation in Medicine: an experience report
Keywords: Educação; Medicina; Habilidades; Pandemia; Narrativa reflexiva; Education; Medicine; Skills; Pandemic; Reflective narrative; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::AVALIACAO DA APRENDIZAGEM